Comparing teaching styles and personality types of efl instructors in the public and private sectors (2011)
This is an exploratory non-experimental research study whose main objective is to compare the teaching styles of a group of thirty teachers of English working in either public or private secondary education in Chile. In order to collect the required data, two instruments were administered to the participants: a teaching style inventory and a personality type index proposed by Grasha. Results indicate that public sector participants show a facilitator teaching style and an extrovert personality type, whereas private sector participants reveal a more authoritative teaching style and an introverted type of personality.Este estudio exploratorio de naturaleza no-experimental tiene como objetivo principal comparar los estilos de enseñanza de un grupo de treinta profesores de inglés que trabajan en el nivel de enseñanza secundario del sistema educativo estatal o privado, en Chile. Para la recolección de datos se utilizaron el inventario de estilos de enseñanza y el índice de tipo de personalidad de Grasha. Los resultados indican que los participantes del nivel de enseñanza estatal presentan un estilo de enseñanza de naturaleza facilitadora y un tipo de personalidad extrovertido, mientras que los participantes del nivel de enseñanza privado revelan un estilo de enseñanza más autoritario y una personalidad más introvertida.